Incidence and characteristics of methicillin-resistant coagulase-negativeStaphylococcus aureusin peritoneal dialysis-associated peritonitis in a single center using molecular methods - Camargo, Carlos Henrique [UNESP]; Ribeiro de Souza da Cunha, Maria de Lourdes [UNESP]; Teixeira Caramori, Jacqueline Costa [UNESP]; Mondelli, Alessandro Lia [UNESP]; Montelli, Augusto Cezar [UNESP]; Barretti, Pasqual [UNESP] (Springer, 2020)
Purpose Peritonitis is a serious complication of peritoneal dialysis and coagulase-negativeStaphylococcus(CNS) is the most frequent cause of peritoneal dialysis (PD)-infections in many centers. This study aimed to investigate the molecular epidemiology of CNS isolated from PD-peritonitis in a Brazilian single center, focusing on the genetic determinants conferring methicillin resistance. Methods Bacterial strains were isolated from peritoneal fluid of patients presenting PD-peritonitis, identified by phenotypic and molecular methods, and those identified as CNS were submitted tomecAdetection, SCCmec, pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST). Results Over the 18-year period of this study (1995-2011), a total of 878 peritonitis episodes were diagnosed in this unit, 115 were caused by coagulase-negative staphylococci of which 72 byStaphylococcus epidermidis.mecAgene was detected in 55 CNS (47.8%), more frequently on the more recent years. SCCmectype III was the most frequent cassette, followed by SCCmectype IV and SCCmectype II. A diverstity of pulsotypes was observed among theS. epidermidisisolates, but five clusters (based on the 80% cutoff) were identified. Diversified sequence types (ST02, ST05, ST06, ST09, ST23, ST59 and ST371) were detected. Conclusions Detection of SCCmectype III among coagulase-negativeStaphylococcusunderscores the role of hospital environments as potential source of methicillin-resistantStaphylococcuscausing peritonitis in PD patients.
Keywords: Bacterial peritonitis; mecA; Peritoneal dialysis; PFGE; Sccmec; Staphylococcus epidermidis